Collisional picture of quantum optics with giant emitters - Dario Cilluffo; Angelo Carollo; Salvatore Lorenzo; Jonathan A. Gross; G. Massimo Palma; Francesco Ciccarello (Physical Review Research, 2020)
The effective description of the weak interaction between an emitter and a bosonic field as a sequence of two-body collisions provides a simple intuitive picture compared to traditional quantum optics methods as well as an effective calculation tool of the joint emitter-field dynamics. Here this collisional approach is extended to many emitters (atoms or resonators), each generally interacting with the field at many coupling points (giant emitter). In the regime of negligible delays, the unitary describing each collision in particular features a contribution of a chiral origin resulting in an effective Hamiltonian. The picture is applied to derive a Lindblad master equation (ME) of a set of giant atoms coupled to a (generally chiral) waveguide field in an arbitrary white-noise Gaussian state, which condenses into a single equation and extends a variety of quantum optics and waveguide QED MEs. The effective Hamiltonian and jump operators corresponding to a selected photodetection scheme are also worked out.